Effects of Dietary Bopu Powder Supplementation on Serum Antioxidant Capacity, Egg Quality, and Intestinal Microbiota of Laying Hens - Liu, Hua; Lin, Qian; Liu, Xiubin; Huang, Peng; Yang, Zihui; Cao, Manhu; Liu, Mengting; Li, Xinyao; Zeng, Jianguo; He, Jianhua (Frontiers in Physiology, 2022)
The purpose of this study was to investigate the effects of dietary Bopu powder supplementation on the serum antioxidant capacity, serum biochemical indices, egg quality and intestinal microbiota. Six hundred and forty-eight 33-wk-old Lohmann Brown commercial laying hens were randomly divided into 6 groups and fed a basal diet supplemented with 0，25，50，100，200，400 mg/kg Bopu powder for 8 weeks, denoted BP0, BP 25, BP50, BP100, BP200 and BP400, respectively. The results showed that dietary Bopu powder supplementation linearly decreased serum CHO concentration (linear, P < 0.01), and increased the serum GLB and ALB concentrations (linear, P < 0.05). In addition, the higher activities of CAT and GSH-Px in serum was observed in BP50 and BP100 groups (P <0.05). Compared with BP0, the egg Haugh Unit were significantly increased in BP25 and BP50 (P <0.05), and egg shell thickness was enhanced in BP25, BP200 and BP400 (P <0.05). The yolk GSH-Px and CAT values significantly improved in Bopu powder supplement groups (25-100mg/kg), while the MAD concentrations significantly decreased (P <0.05). Dietary supplementation with Bopu powder at dose of 25 to 100 mg/kg significantly increased the GSH-Px and CAT activities and significantly decreased the MAD concentrations in the yolk (P <0.05). Besides, Bopu powder supplementation increased diversity of microbiota and the relative abundance of Bacteroidota in foregut. Especially, dietary 25 to 50 mg/kg Bopu powder supplementation significantly increased the relative abundance of Enterococcus, Bacteroides and Fusobacterium in the foregut. Dietary 50 to 100 mg/kg Bopu powder supplementation increased the relative abundance of Lactobacillus in the hindgut. In conclusions, dietary Bopu powder supplementation improved the egg quality and antioxidant capacity of laying hens, and increased the abundance of beneficial bacteria in foregut. Moreover, the appropriate amount of Bopu powder additive in the laying hen diet was 25-50mg/kg.